T-cell receptor repertoire of cytomegalovirus-specific cytotoxic T-cells after allogeneic stem cell transplantation - Takashi Toya (Nature Portfolio, 2020)
Abstract Cytomegalovirus (CMV) infection is a major complication during allogeneic stem cell transplantation (allo-SCT). However, mechanisms of adaptive immunity that drive this remain unclear. To define early immunological responses to CMV after transplantation, we using next-generation sequencing to examine the repertoire of T-cell receptors in CD8+/CMV pp65 tetramer+ cells (CMV-CTLs) in peripheral blood samples obtained from 16 allo-SCT recipients with HLA-A*24:02 at the time of CMV reactivation. In most patients, TCR beta repertoire of CMV-CTLs was highly skewed (median Inverse Simpson’s index: 1.595) and, 15 of 16 patients shared at least one TCR-beta clonotype with ≥ 2 patients. The shared TCRs were dominant in 12 patients and, two clonotypes were shared by about half of the patients. Similarity analysis showed that CDR3 sequences of shared TCRs were more similar than unshared TCRs. TCR beta repertoires of CMV-CTLs in 12 patients were also analyzed after 2–4 weeks to characterize the short-term dynamics of TCR repertoires. In ten patients, we observed persistence of prevailing clones. In the other two patients, TCR repertoires became more diverse, major clones declined, and new private clones subsequently emerged. These results provided the substantive clue to understand the immunological behavior against CMV reactivation after allo-SCT.